Analysis of the Causes and Countermeasures of Chengdu City Road Traffic Noise. Issue 1 (October 2020) - Chen, Li Chun; Bo, Fang; Xu, He; Cai, Jie; Li, Dong
Abstract: As the pace of urbanization in Chengdu continues to accelerate, the construction of urban roads has also been strengthened.2015 forming a dense urban road network. People often say that the city is too noisy. In fact, from a professional point of view, it is urban road noise. Therefore, under the influence of more and more people from urban road noise, it is necessary to investigate the generation and impact of urban road noise and related prevention measures. This article explains the causes and hazards of Chengdu's road noise, and puts forward opinions and suggestions on urban road noise in order to provide some research materials for the same type of urban noise prevention.